Economic costs attributable to modifiable risk factors: an analysis of 24 million urban residents in China - Xiong, X; Huo, Z; Zhou, Y; Bishai, DM; Grépin, KA; Clarke, PM; Chen, C; Luo, L; Quan, J (BioMed Central, 2024)
Background: Estimating the economic burden of modifiable risk factors is crucial for allocating scarce healthcare resources to improve population health. We quantified the economic burden attributable to modifiable risk factors in an urban area of China. Methods: Our Shanghai Municipal Health Commission dataset covered 2.2 million inpatient admissions for adults (age ≥ 20) in public and private hospitals in 2015 (1,327,187 admissions) and 2020 (837,482 admissions). We used a prevalence-based cost-of-illness approach by applying population attributable fraction (PAF) estimates for each modifiable risk factor from the Global Burden of Diseases Study (GBD) to estimate attributable costs. We adopted a societal perspective for cost estimates, comprising direct healthcare costs and productivity losses from absenteeism and premature mortality. Future costs were discounted at 3% and adjusted to 2020 prices. Results: In 2020, the total societal cost attributable to modifiable risk factors in Shanghai was US$7.9 billion (95% uncertainty interval [UI]: 4.6–12.4b), mostly from productivity losses (67.9%). Two health conditions constituted most of the attributable societal cost: cancer (51.6% [30.2–60.2]) and cardiovascular disease (31.2% [24.6–50.7]). Three modifiable risk factors accounted for half of the total attributable societal cost: tobacco (23.7% [16.4–30.5]), alcohol (13.3% [8.2–19.7]), and dietary risks (12.2% [7.5–17.7]). The economic burden varied by age and sex; most of the societal costs were from males (77.7%), primarily driven by their tobacco and alcohol use. The largest contributor to societal costs was alcohol for age 20–44, and tobacco for age 45 + . Despite the COVID-19 pandemic, the pattern of major modifiable risk factors remained stable from 2015 to 2020 albeit with notable increases in attributable healthcare costs from cancers and productivity losses from cardiovascular diseases. Conclusions: The substantial economic burden of diseases attributable to modifiable risk factors necessitates targeted policy interventions. Priority areas are reducing tobacco and alcohol consumption and improving dietary habits that together constitute half of the total attributable costs. Tailored interventions targeting specific age and sex groups are crucial; namely tobacco in middle-aged/older males and alcohol in younger males.